Work-Family Enrichment: Does It Help Manage Emotional Exhaustion During The COVID-19 Pandemic? - Jannah, Syayyidah Maftuhatul; Prajasari, Anniza Citra; Setyorini, Noni (The South East Asian Journal of Management, 2022)
Research Aims: This study aims to analyse the role of work-family enrichment on emotional labour and the impact of emotional exhaustion during the COVID-19 pandemic. Design/methodology/approach: The type of data collected is primary data that uses an online questionnaire. The sampling method is a purposive sampling technique. The PLS-SEAM is used to analyse the collected data. Research Findings: Work-family enrichment and family-work enrichment had a positive and significant effect on emotional labour (surface acting and deep acting) and on emotional exhaustion. Theoretical Contribution/Originality: The results of this study show the importance of the role of work and family enrichment to employees during this pandemic. That is, work and family support can give positive energy to manage their unstable emotions and reduce or even prevent some people from emotional exhaustion. Managerial Implication in the South East Asian Context: Organisations should concern with friendly-family policies that can fulfil work-family enrichment of employees. Employees will be more loyal to work and be more vigorous and thrive in the workplace, so it can reduce turnover. Research limitation & Implications: This study has not classified the workforce based on the WFH policy. The respondents could not differentiate between those who were WFH and those who were not. There seems to be a possibility that this can also affect work-family enrichment and emotional exhaustion.